Zakat Wakaf (Ziswa): Solusi dalam Mewujudkan Pemberdayaan Umat - Sri Lumatus Sa'adah (IQTISHODUNA: Jurnal Ekonomi Islam, 2017)
Zakat is believed as a worship that serves to balance social relations. Through zakat wakaf (ziswa), the distance between the person is located and the disadvantaged person can be brought closer. People have an obligation to help and care for the hard people who live around them. In addition, ziswa also works so that the circulation of wealth is not just spinning among a group of people just standing. By learning, people are actively participating in empowering the economically disadvantaged societies. That goal can be realized if zakat is managed with professional management, accountable, and modern. Zakat has been managed by zakat fund management institutions.